Fava bean plant performance and fertility dynamics in Mars regolith simulant-based substrates for space farming - Caporale, Antonio Giandonato; Paradiso, Roberta; Arouna, Nafiou; Amitrano, Chiara; Tagliamonte, Silvia; Chiacchio, Manuela Flavia; Vitaglione, Paola; De Pascale, Stefania; Adamo, Paola (Frontiers in Plant Science, 2025)
IntroductionPlants are promising bioregenerators for long-term space missions. However, space cultivation will require fertile substrates based on in-situ available materials.MethodsWe assessed the response of fava bean (Vicia faba L. cv. 'Sfardella') to glasshouse cultivation on six substrates: pure MMS-1 Mars regolith simulant (R100), MMS-1 amended with green compost 70:30 v:v (R70C30), pure fluvial sand (S100), sand mixed with compost 70:30 v:v (S70C30), sandy-loam volcanic soil (VS), and clay red soil (RS). Plant physiological and growth parameters, nutritional and nutraceutical profile of seeds, and nutrient bioavailability in the substrates, before and after cultivation, were determined.ResultsNet photosynthesis was lower in plants in pure regolith, while the addition of compost restored assimilation at a similar rate to that of the other substrates. Both regolith-based substrates reduced the biomass accumulation, but seed production improved in R70C30 (+61.9% than R100), giving similar yield compared to VS and S70C30. The chemical fertility and nutrient bioavailability improved after cultivation of the fava bean Fabaceae crop in succession to potato (e.g., in R100, +52% organic C, +19% N, and +27% S). The easily bioavailable nutrients declined over time, while the potentially bioavailable fraction increased, indicating a strengthening interaction with the substrate adsorption surface.DiscussionThe growth on pure regolith simulant MMS-1 reduced the plant growth and seed production; however, the amendment with green compost improved the nutrient bioavailability of MMS-1, with positive effects on the yield, harvest index, and nutritional quality of fava bean seeds, at similar level to volcanic soils.